Budaya Kerja dan Disiplin Kerja dalam Mewujudkan Kepuasan Kerja Pegawai di Sekretariat Daerah Kabupaten Agam - Malini Syaftia Rahmawati; Aldri Frinaldi (Jurnal Public Policy, 2021)
Work culture aims to create employee effectiveness and efficiency at work. The realization of this must be supported by the existence of good employee work discipline. This will give satisfaction to employees. However, there are still many employees who do not understand the work culture in the institutions they work for, apart from that delays in employee attendance that often occur without strict sanctions cause problems not only for the employees themselves, but also disrupt cooperation between employees in carrying out their duties and responsibilities. which has been given. This study aims to prove whether or not the influence of work culture and work discipline variables on employee job satisfaction at the Regional Secretariat of Agam Regency is present or not. The research method used in this research is survey-based quantitative. The sample was determined using a total sampling technique. The research instrument used was a questionnaire that had been tested for validity and reliability. The collected data were analyzed using the T test and F test. Based on the results of the research that had been done, it was found that there was an influence of work culture and work discipline variables either partially or simultaneously on job satisfaction which could be trusted to be 100% correct. The results of the research which states that the influence of the independent variable on the dependent variable requires affirmation of work culture and strict enforcement of work discipline towards employees. It aims to make employees feel satisfied at work, so that it will have an impact on their effective and efficient work results.